Is God to blame? : moving beyond pat answers to the problem of evil - Boyd, Gregory A., 1957- (Downers Grove, Ill. : InterVarsity Press, 2003)
A pastoral theologian challenges traditional assumptions about God and suffering, arguing that God's glory is revealed not as compelling power but as sacrificial love
The lie and the truth -- Evil and the blueprint -- Freedom and risk -- Complexity and war -- Omnipotence and two variables -- Prayer and ambiguity -- Life and hope -- Mercy and hardening -- Providence and control
Includes bibliographical references (pages 198-205) and index
Keywords: Theodicy; Good and evil; Spiritual warfare